Gene Mutation Spectrum of Thalassemia Among Children in Yunnan Province - Huang, Ti-Long; Zhang, Tian-Yao; Song, Chun-Yan; Lin, Yun-Bi; Sang, Bao-Hua; Lei, Qing-Ling; Lv, Yu; Yang, Chun-Hui; Li, Na; Tian, Xin; Yang, Yue-Huang; Zhang, Xian-Wen (Frontiers in Pediatrics, 2020)
Background: Thalassemia is an autosomal genetic disorder, found through out the world. It is still not treatable and create socio economic problems. In this study, we investigated the prevalence and spectrum features of thalassemia in Yunnan Province, the southwestern area of China. During 2014 to 2018, a total of 3539 suspected thalassemia children were detected with α‐ and β‐thalassemia mutations by gap‐Polymerase Chain Reaction (PCR) and reverse dot blot (RDB) analysis in Kunming Children’s Hospital. Results: Of these patients, 1130 were diagnosed thalassemia gene carriers with a carrying rate of 31.92%. Among them, α‐thalassemia was 43.63%, β-thalassemia was 53.98%, cases with both α- and β- thalassemia was 2.39%. In α-thalassemia patients, the most common mutations was –SEA/αα (52.13%), followed by -α3.7/αα(27.79%), hemoglobin H disease (18.46%) and -α4.2/αα (1.62%). 15 gene mutations and 30 genotypes were identified in β-thalassemia patients, with the five most common mutations CD17 (A＞T) (29.51%), CD41–42 (-TTCT) (27.87%), IVS-II-654(C＞T) (14.92%), CD26 (G＞A) (6.89%), and CD26/CD27 (2.62%) accounting for 81.81% of the β-globin gene mutations. Furthermore, we founded two rare mutations CD34 (TGG → TAG) and Int in Chinese populations. Conclusions: Our results suggested that the prevalence and gene mutation spectrum of thalassemia display obviously heterogeneity among children in Yunnan Province. The findings provide the valuable information for premarital and pre-pregnancy screening, prenatal diagnostic services, and designing appropriate prevention programs to control thalassemia for future in this area.